Control Of Spodoptera Frugiperda Using Insecticides Applied With Drones And Spray Boom - Zhiminaicela Cabrera, Jonathan Bladimir; Herrera-Reyes, Sayda; España Valencia, Paola (Universidad Pedagógica y Tecnológica de Colombia, 2024)
In this study, different treatments, and application methods for pest control in maize cultivation were evaluated. Variables such as the percentage of pest incidence, the degree of crop infection according to the DAVIS scale, and the number of larvae at different days of application were analyzed. The results showed that treatments with a dose of 200 cc/ha, whether applied by drone or conventionally, were the most effective in terms of pest incidence and crop infection degree. At 5 days after application, a significant decrease in the number of larvae was observed in the treatments with a dose of 200 cc/ha applied by drone. However, at 7 and 10 days, a moderate increase in the number of larvae was recorded in all treatments. Furthermore, it was found that drone-based application allowed for better product dispersion and greater coverage in the treated area. These findings highlight the importance of considering the dose and application method to achieve effective pest control in maize cultivation